Cutting Costs, Boosting Quality and Collecting Data Real-Time : Lessons from a Cell Phone-Based Beneficiary Survey to Strengthen Guatemala’s Conditional Cash Transfer Program - Schuster, Christian; Perez Brito, Carlos (World Bank, Washington, DC, 2012)
A 2010 country governance and Anti-Corruption (CGAC) funded pilot in Guatemala employed entry-level mobile phones in conjunction with Episurveyor, a free, web-based software for data collection, to drastically reduce costs, facilitate accuracy and accelerate implementation of a nationally-representative beneficiary survey of Guatemala's conditional cash transfer program. As such it illustrates the potential of mobile phone-based data collection to strengthen program monitoring, evaluation and implementation, in particular in remote and marginalized areas highly populated by indigenous peoples.